Ion Beam Stimulation Therapy With a Nanoradiator as a Site-Specific Prodrug - Kim, Jong-Ki; Seo, Seung-Jun; Jeon, Jae-Geun (Frontiers in Physics, 2020)
In view of the fact that Bragg peak energy cannot be delivered individually to multiple scattered infiltrating tumors or diffuse lesions, the energy of the ion beam could instead be adjusted to traverse the entire body for the selective activation of nanoparticles (NPs) inside the target lesions with an ion fluence comparable to the Bragg peak. This Coulomb stimulation of NPs generates low-energy electrons (LEEs) and characteristic fluorescent X-rays (XFLs) from the NP surface; this effectively transforms inert NPs into nanoradiators, much like the conversion of a prodrug into a drug. In contrast, the relatively small plateau dose absorbed along the beam path ensures that there are minimal effects to normal tissue (NT). This simple but innovative approach enables unprecedented traversing ion beam stimulation therapy (TIBS) for infiltrating tumors or diffuse non-oncological lesions. The theoretical background and efficacy of TIBS has been demonstrated by several proof-of-concept studies with animal disease models and molecular-targeted high-Z NPs.